A methodological note on the global Multidimensional Poverty Index (MPI) 2022 changes over time results for 84 countries - Alkire, S; Kanagaratnam, U; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2022)
This Methodological Note presents the methodology and policies that underlie the changes over time in multidimensional poverty for 84 countries. 35 of the 84 countries have trends for three points in time; while poverty trends in 48 countries are based on two points in time. Gambia is the only country where we have presented results for four points in time.